Ideologia, conformismo e subjetivação nos Cadernos do cárcere - Agostinho, Thiago Lira Alves (2023)
One of the most problematic issues in political theory is the question of obedience and consent, that is, the ways and motivations in which people subject themselves to their own loss of freedom, or, one might say, “conform” to the current order. Continuing this reflection, the question centered on this research brings to light the innovative contributions of Antonio Gramsci’s Marxism in the notes of the Quaderni del carcere dedicated to the study of ideology, which can be considered the political-practical link of hegemony and, therefore, a central element in the production of social conformism and subjectivation, that is, the process of constituting subjectivity. In this sense, we are interested in investigating the extent to which Gramsci’s philosophy converges not only to the appropriation of Marx’s legacy, but also and above all, represents an original contribution by the Italian author to elucidate how ideologies, in addition to constituting themselves in the process of assent to domination, can carry its opposite, that is, the formation and political emancipation, depending on the class that raises and develops them. In other words, our investigation questions the extent to which ideologies can be instruments of the will to create a new culture, the diffusion of new worldviews and an “active conformism”. In short: the concept of ideology in Gramsci shows how its double orientation, gnosiological and axiological, can encourage the constitution of new subjectivities, thought of in the concrete horizon of a new conformism capable of spreading as a mass conception for subordinate classes. In doing so, the subordinate classes become a new political subject, which creates its own hegemony through the “philosophy of praxis”, the integral unity between theory and practice, whose foundation is absolute historicism. With that, Gramsci argues with the conservative view of the historicism of the moderates, carrying out a powerful critique of the neo-idealist philosophy of Benedetto Croce, in addition to the Marxist positivism that was spreading in the Second International. The philosophy of praxis constitutes an instrument for lucid analyzes of fascism, questioning the naturalized conceptions of the world, but insofar as these are situated in historical time, they can be overcome by the same instrument, now as mass philosophy. From this results, above all, the power present in the concept of ideology that is presented in the Quaderni, performing a consequent function for philosophy and for the science of politics: the constitution of political subjects, which are realized in self-government, no longer through the subalternity of class. Such a vision of politics may prove to be utopian for the dominant tradition of political thought, but for the author of the Quaderni it is not only possible, but imposes itself as a historical necessity for subaltern classes and groups, seeking to implement their emancipatory ideology in concrete social relations.